Studi Eksegesis: “Apa Yang Dipersatukan Allah Tidak Boleh Diceraikan Manusia” Dalam Matius 19:6 - Pelealu, Nadia (Vieka Wahana Semesta, 2024)
Abstract: This research discusses what God has joined together and what man should not divorce in Matthew 19:6 (exegesis study). This command of God refers to the concept of marriage and divorce. In reality, many Christian couples face various problems that sometimes lead to divorce, and some to adultery. God clearly says that